Elastic transverse electron scattering form factors of 11Li exotic nucleus - Hameed, B. S. (Iraqi Journal of Physics, 2019)
The elastic transverse electron scattering form factors have been studied for the 11Li   nucleus using the Two- Frequency Shell Model (TFSM) approach. The single-particle wave functions of harmonic-oscillator (HO) potential are used with two different oscillator parameters bcore and bhalo. According to this model, the core nucleons of 9Li nucleus are assumed to move in the model space of spsdpf. The outer halo (2-neutron) in 11Li is assumed to move in the pure 1p1/2, 1d5/2, 2s1/2 orbit. The shell model calculations are carried out for core nucleons using the spsdpf-interaction.  The elastic magnetic electron scattering of the stable 7Li and exotic 11Li nuclei are also investigated through Plane Wave Born Approximation (PWBA). It is found that the difference between the total form factors of unstable isotope (11Li halo) and stable isotope 7Li is in magnitude. The measured value of the magnetic moment is also reproduced.